Effect of Oxytocin on Hunger Discrimination - Head, Mitchell A.; Jewett, David C.; Gartner, Sarah N.; Klockars, Anica; Levine, Allen S.; Olszewski, Pawel K. (Frontiers in Endocrinology, 2019)
Centrally and peripherally administered oxytocin (OT) decreases food intake and activation of the endogenous OT systems is associated with termination of feeding. Evidence gathered thus far points to OT as facilitator of early satiation, thus, a peptide that reduces a meal that has already begun. It is not known, however, whether OT can diminish a feeling of hunger, thereby decreasing a perceived need to seek calories. Therefore, in the current project, we first confirmed that intraperitoneal (i.p.) OT at 0.3-1 mg/kg reduces food intake in deprived and non-deprived rats. We then used those OT doses in a unique hunger discrimination protocol. First, rats were trained to discriminate between 22- and 2-h food deprivation (hungry versus sated state) in a two-lever operant procedure. After rats acquired the discrimination, they were food-restricted for 22 h and given i.p. OT before a generalization test session. OT did not decrease 22-h deprivation-appropriate responding to match that following 2-h food deprivation, thus, it did not reduce the perceived level of hunger. In order to better understand the mechanisms behind this ineffectiveness of OT, we used c-Fos immunohistochemistry to determine whether i.p. OT activates a different subset of feeding-related brain sites under 22- versus 2-h deprivation. We found that in sated animals, OT induces c-Fos changes in a broader network of hypothalamic and brain stem sites compared to those affected in the hungry state. Finally, by employing qPCR analysis, we asked whether food deprivation versus sated state have an impact on OT receptor expression in the brain stem, a CNS ‘entry’ region for peripheral OT. Fasted animals had significantly lower OT receptor mRNA levels than their ad libitum-fed counterparts. We conclude that OT does not diminish a feeling of hunger before a start of a meal. Instead OT’s anorexigenic properties are manifested once consumption has already begun which is - at least to some extent - driven by changes in brain responsiveness to OT treatment in the hungry versus fed state. OT should be viewed as a mediator of early satiation rather than as a molecule that diminishes perceived hunger.